Assessment of ionizable, zwitterionic oximes as reactivating antidotal agents for organophosphate exposure. (1st August 2019) - Taylor, Palmer; Yan-Jye, Shyong; Momper, Jeremiah; Hou, William; Camacho-Hernandez, Gisela Andrea; Radic', Zoran; Rosenberg, Yvonne; Kovarik, Zrinka; Sit, Rakesh; Sharpless, K. Barry
Abstract: Since the development in the 1950's of 2-PAM (Pralidoxime), an antidote that reactivates organophosphate conjugated acetylcholinesterase in target tissues upon pesticide or nerve agent exposure, improvements in antidotal therapy have largely involved congeneric pyridinium aldoximes. Despite seminal advances in detailing the structures of the cholinesterases as the primary target site, progress with small molecule antidotes has yet to define a superior agent. Two major limitations are immediately apparent. The first is the impacted space within the active center gorge, particularly when the active center serine at its base is conjugated with an organophosphate. The reactivating nucleophile will have to negotiate the tortuous gorge terrain to access the phosphorus atom with its most nucleophilic form or ionization state, the oximate anion. A second limitation stems from the antidote crossing the blood-brain barrier sufficiently rapidly, since it is well documented that central acetylcholinesterase inhibition gives rise to cardiovascular and respiratory compromise. The associated hypoxia then leads to a sequelae of events, including poor perfusion of the brain and periphery, along with muscle fasciculation, tremors and eventually seizures. We consider both the barriers confronting and further achievements necessary to enhance efficacy of antidotes.